Rudimentary Horn Pregnancy Misleading Abdominal Missed Abortion - Biswas, Sankar Prosad; Das, Bishwajit; Akter, Shahanaj (Journal of Medicine, 2014)
Pregnancy in a rudimentary horn is a very rare condition. It is responsible for severe complications and also a life threatening condition as it mostly terminates by rupture of pregnancy. This was a case of non communicating unruptered pregnancy which was misdiagnosed on 1st and 2nd transabdominal ultrasonography, progressing to 22weeks gestation and ends in a missed abortion. A transvaginal ultrasonography revealed it as an abdominal pregnancy and on laparotomy confirmed diagnosis was non communicating rudimentary horn pregnancy. Pregnancy sac with foetus was removed intact and patient. recovered without any complications. Gravid rudimentary horn may be misdiagnosed as abdominal pregnancy and are of interest in management. DOI: http://dx.doi.org/10.3329/jom.v15i1.19879 J Medicine 2014; 15: 74-76